Hydrodynamic modeling and time-resolved imaging reflectometry of the ultrafast laser-induced ablation of a thin gold film. (June 2020) - Olbrich, M.; Pflug, T.; Wüstefeld, C.; Motylenko, M.; Sandfeld, S.; Rafaja, D.; Horn, A.
Highlights: A 150 nm thick thin film of gold deposited on 5 mm fused silica substrate, which was covered by an adhesion layer of about 20 nm chromium, was irradiated with single-pulsed ultrafast laser radiation in the gentle ablation regime (wavelength λ = 800 nm, pulse duration τH = 40 fs, peak fluence H 0 = 1.4 J/cm 2 ) The resulting ablation structure features a flat topology with a constant ablation depth of approximately 70 nm in the center surrounded by a lamella-like structure with an irregular morphology The optical response of the excited gold thin film was measured by ultrafast imaging reflectometry up to a delay time of 3.8 ns between the pump and the probe radiation (wavelength λ = 440 nm, pulse duration τH = 60 fs, angle of incidence θ = 56 ∘ ) The constant ablation depth is explained by quasi-two-dimensional two-temperature hydrodynamic modeling by the interference of two rarefaction waves Excellent agreement between the simulated and experimentally determined topology of the ablation structure The optical response reveals five stages of excitation, being completely explainable by modeling Abstract: The ablation of thin metal films using ultrafast laser radiation represents a standard processing procedure in laser technology. However, looking closer to the resulting structures, the arising topology deviates strongly from the expected one. Ablation of thin gold films using ultrafast laser radiation with a Gaussian-shaped spatial intensity distribution results in flat topologies. By synergistically combining space and time-resolved reflectometry with expanded two-temperature hydrodynamic modeling, we explain the formation of bulging and rupture of the thin film-surface by the expansion of strongly stretched liquid material due to the induced rarefaction wave propagating towards the substrate. Also, the formation of a flat ablation structure is described by the interplay of two rarefaction waves, one propagating towards the substrate and the other one propagating towards the vacuum boundary, within the completely molten film. The simulated topology agrees excellent with the experimentally observed ablation structure. Besides, all simulated stages of excitation of the gold film, namely electron-phonon non-equilibrium, hydrodynamic expansion, and rupture, are confirmed by space and time-resolved pump-probe reflectometry.